Reconstruction of Partial Vermilion Defects with Mucosal Transposition Flap - Süleyman Taş (Haseki Tıp Bülteni)
Aim: Lip, located in lower 1/3 of the face, is very important unit from aesthetic and functional aspect. Vermilion is a subunit of the lip and also has aesthetic and sensorial functions. Following the trauma and cancer surgeries, vermilion reconstruction is needed and it needs experienced and meticulous procedures. Here, it is aimed to describe the experience of mucosal transposition flap in reconstruction of partial vermilion defects with a detailed operation technique, the results of the patients and review of the literature. Methods: Between February 2014 and May 2015, nine patients (eight male, one female; mean age 45, range 34 to 52) were diagnosed precancerous lesion with punch biopsy and were underwent a surgical excision and vermilion reconstruction under local anesthesia. The patients were followed up 1 year with a interval of postoperative 7. 7. day and 1, 3, 6 and 12. month. The histopatologic, functional and aesthetic records were evaluated. Results: Functional and excellent aesthetic results were achieved in all patients. No complication nor recurrence was observed during follow-up period. Conclusion: Oral mucosal transposition flap was considered as first choice in reconstruction of the partial vermilion defects since its functional and aesthetic success and no donor tissue morbidity.